Polysaccharides From Abrus cantoniensis Hance Modulate Intestinal Microflora and Improve Intestinal Mucosal Barrier and Liver Oxidative Damage Induced by Heat Stress - Wang, Ying; Sun, Wenjing; Wu, Enyun; Wang, Kaijun; Chen, Xiaogang; Cui, Yao; Zhang, Geyin; Lv, Feifei; Wang, Yuhan; Peng, Xiaomin; Si, Hongbin (Frontiers in Veterinary Science, 2022)
The protective effects of polysaccharides from Abrus cantoniensis Hance (ACP) on antioxidant capacity, immune function, the hypothalamus-pituitary-adrenal (HPA) axis balance, the intestinal mucosal barrier, and intestinal microflora in heat stress (HS)-induced heat-injured chickens are rarely reported. The purpose of this study was to investigate the protective effects of ACP on HS-injured chickens by enhancing antioxidant capacity and immune function, repairing the intestinal mucosal barrier, and regulating intestinal microflora. A total of 120 native roosters in Guangxi were randomly divided into 5 groups to evaluate the protective effect of ACP on chickens injured by HS (33 ± 2°C). The results showed that ACP increased the body weight and the immune organ index of heat-injured chickens, regulated the oxidative stress kinase secretion, and restored the antioxidant level of heat-injured birds. ACP significantly inhibited the secretion of corticotropin releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosterone (COR) and reversed the disorder of hormone levels caused by HS. ACP significantly regulated the secretion levels of immune cytokines and restored the immune function of the body. ACP significantly improved the intestinal morphology and increased the expression levels of tight junction proteins, which had a positive effect on protecting intestinal health. The results of high-throughput sequencing of the 16S rRNA gene showed that HS led to an increase in the abundance of harmful bacteria and an abnormal increase in the abundance of intestinal microflora and that ACP restored the HS-induced intestinal microflora imbalance. In conclusion, this study provides a scientific basis for ACP as an antioxidant activity enhancer to reduce liver injury, regulate intestinal microflora, and protect intestinal mucosal damage in chickens.